2016
DOI: 10.3390/ijerph13010137
|View full text |Cite
|
Sign up to set email alerts
|

Using a Household Food Inventory to Assess the Availability of Traditional Vegetables among Resettled African Refugees

Abstract: A cross-sectional sequential explanatory mixed methods study was conducted among household food preparers to examine the association between home availability and consumption of traditional vegetables among resettled African refugees living in Queensland, Australia. Home availability of traditional African vegetables was associated with age, having a vegetable garden, employment status, and having a supermarket in the local neighborhood. Food preparers from homes with low vegetable availability were less likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(52 citation statements)
references
References 31 publications
1
51
0
Order By: Relevance
“…The included studies involved a diverse range of ethnicities; the majority focused on refugees originating from countries in three distinct regions: Southeast Asia (Laos, Vietnam, Cambodia, and Hmong refugees), sub‐Saharan Africa (Sudan, Somalia, Democratic Republic of the Congo, Burundi, Djibouti Kenya, Tanzania, Eritrea, and Ethiopia), and Middle Eastern countries (Afghanistan, Iran, and Iraq). Most of the studies were conducted in Australia 18,54–58,72–74 or the United States of Ameirca 22,23,25,28,29,59,60,69,70,71 . No study was conducted in the United Kingdom.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies involved a diverse range of ethnicities; the majority focused on refugees originating from countries in three distinct regions: Southeast Asia (Laos, Vietnam, Cambodia, and Hmong refugees), sub‐Saharan Africa (Sudan, Somalia, Democratic Republic of the Congo, Burundi, Djibouti Kenya, Tanzania, Eritrea, and Ethiopia), and Middle Eastern countries (Afghanistan, Iran, and Iraq). Most of the studies were conducted in Australia 18,54–58,72–74 or the United States of Ameirca 22,23,25,28,29,59,60,69,70,71 . No study was conducted in the United Kingdom.…”
Section: Resultsmentioning
confidence: 99%
“…Many sub‐Saharan African refugee parents reported that language acted as a barrier to the purchase of healthy food (i.e., the inability to read labels in English) and it also shaped their food shopping patterns, by limiting the foods they recognised or knew how to cook without reading instructions. This subsequently affected their children's diet 57 . An additional study found that children of sub‐Saharan African refugee parents with low English competency reported a greater intake of ‘soda’ and ‘snacks’ as these were preprepared and obviated the need to read instructions 71 .…”
Section: Resultsmentioning
confidence: 99%
“…This category covered 8 studies 17,[20][21][22][23]25,27,28 which presented aspects related to social, cultural, political and economic difficulties of access to food in refugee detention centers, refugee camps and in settlement destination countries.…”
Section: Food Inequitymentioning
confidence: 99%
“…The results showed that age, employment, cultivation of vegetables and access to supermarkets in the neighborhood were factors that allowed access to traditional foods of the African culture. It is also pointed out that the language and the fact of having to seek access to food in other neighborhoods are impeding factors in accessing their food of preference 22 .…”
Section: Food Inequitymentioning
confidence: 99%
See 1 more Smart Citation